2018
DOI: 10.1158/1538-7445.am2018-5879
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5879: Effect of Minnelide, a prodrug, on cervical cancer growth

Abstract: Human Papilloma Virus (HPV) infection is associated with the development of Cervical cancer. Therapeutic resistance and recurrence remain the major obstacle to successful treatment of cervical cancer patients. Recently, a novel pro-drug Minnelide, derived from the diterpenoid triepoxide, triptolide, was found to be very effective against several human cancers in experimental animal models. The goal of the present study is to determine the effect of triptolide (in vitro) or Minnelide (in vivo) on HPV positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For male mice, 400 μg/kg/d could increase germ cell degeneration and exfoliation in testes, but both 100 and 200 μg/kg/d had no significant effect on testes after treatment with minnelide for 2 weeks. Previous studies demonstrated that 200 μg/kg/d minnelide treatment for 5 weeks had no significant effect on the body weight of mice [45], and 0.21 μg/kg/d minnelide treatment for 2 weeks did not affect the blood indexes of mice [19]. Meanwhile, Minneamrita Therapeutics LLC initiated many clinical trials (NCT01927965, NCT03117920, NCT03129139, and NCT03760523) for minnelide [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For male mice, 400 μg/kg/d could increase germ cell degeneration and exfoliation in testes, but both 100 and 200 μg/kg/d had no significant effect on testes after treatment with minnelide for 2 weeks. Previous studies demonstrated that 200 μg/kg/d minnelide treatment for 5 weeks had no significant effect on the body weight of mice [45], and 0.21 μg/kg/d minnelide treatment for 2 weeks did not affect the blood indexes of mice [19]. Meanwhile, Minneamrita Therapeutics LLC initiated many clinical trials (NCT01927965, NCT03117920, NCT03129139, and NCT03760523) for minnelide [47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researchers have processed the triptolide to produce minnelide [8]. Minnelide is a water-soluble prodrug of triptolide, which has shown significant therapeutic effects against a large number of cancers in preclinical studies [2,23,35,45]. In the body, minnelide is rapidly converted into triptolide in the presence of alkaline phosphatase [8].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid conversion of Minnelide into active triptolide in vivo (12) and its documented accumulation in brain tissues (30), we next assessed the efficacy of Minnelide in orthotopic mouse MB models. Minnelide was administered in these experiments at previously reported dosages (12,(32)(33)(34)(35). Mice orthotopically implanted with luciferase-expressing G3 MB cells (HD:MB03) were exposed to vehicle or Minnelide.…”
Section: The Triptolide Pro-drug Minnelide Shows Efficacy In Pre-clin...mentioning
confidence: 99%
“…While Minnelide and triptolide demonstrated similar EC50s ex vivo, differences in in vivo efficacy were noted. These variations could arise in part from the administration of a lower effective dose of Minnelide, though the regimen used was supported by previous Minnelide pre-clinical studies (12,(32)(33)(34)(35). Due to differences in molecular weights, 0.7 molar equivalents of Minnelide were administered relative to triptolide when 0.4 mg/kg dose levels were administered for each agent.…”
Section: The Triptolide Pro-drug Minnelide Shows Efficacy In Pre-clin...mentioning
confidence: 99%
“…These events are crucial for progression from high-grade premalignant lesions to cervical cancer. [37][38][39][40][41]…”
Section: Pathogenesis Of Cin and Cervical Cancermentioning
confidence: 99%